Exploring Short Story as Learning Media for Teaching Intensive Reading To 11th Grade English Students - Andieny Ratu Saputra (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study explores the use of short story as a teaching learning medium in intensive reading class of eleventh-grade students at SMA Al Azhar 3 Bandar Lampung. Employing a qualitative research approach, data were collected through observations and questionnaires. The findings reveal a significant improvement in students’ ability to engage with and comprehend intensive reading activities using short story. Most participants demonstrated positive results on understanding of the storylines, better analytical skills, and increased engagement during the learning process. Supporting by questionnaire responses which highlighted that short story made the lessons more enjoyable, supporting media as reading comprehension, fostered creative thinking, and assisted students in identifying key points and drawing conclusions from texts. Additionally, students reported heightened motivation and enthusiasm for learning. However, the study's scope is limited, as it does not fully evaluate the long-term effectiveness of short story as a teaching tool. Further research is recommended to establish best practices and optimize the integration of short story into intensive reading instruction.